ANALISA PENGETAHUAN PENGUNJUNG TENTANG ANTIBIOTIK ORAL TANPA RESEP DOKTER DI APOTEK X JAKARTA TIMUR - Fachdiana Fidia; Siti Aisyah; Marta Halim; Dwi Uswatun Hasanah (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
The relatively high use of Antibiotics can cause various problems and is a global threat to health. Lack of public knowledge about the correct use of antibiotics and knowledge of innapproriate antibiotics are factors that can trigger resistance. Antibiotic resistance has become a global problem. Some studies say antibiotic resistance is increasing. This is due to a lack of knowledge about the use of antibiotics and many pharmacies that sell antibiotics without a doctor’s prescription. The purpose of the study was to determine the overview of the visitor concering antibiotics oral without doctor prescription on pharmacy X East Jakarta. The research method used is descriptive and using accidental sampling techniques. The data analyzed include: the definition of antibiotic, how to use antibiotic, side effect of antibiotic, indication of antibiotic. The results of this research obtained 154 respondents is using antibiotic withouh doctor prescription and knowledge level concerning antibiotic is 49 respondent (32 %) have a good knowledge, 84 respondent (55%) have a sufficient knowledge and 21 respondent (13%) have a less knowledge. These results indicate that knowledge of the visitors belongs to the sufficient category.